Oral history and narrative as methodologies for addressing state terrorism, 20th century in Argentina. - Jean Jean, Melina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The objective of this paper is to reflect upon the possibilities and specificities of working with oral sources through the use of oral history and narrative as a methodology in the study of the memories based on the investigation of a case study. The project is about representations of people who disappeared and/or were assassinated and is called 《Mosaicos por la Memoria》 (Mosaics for Memory) of the Space of Culture and Memory, el Rancho Urutaú, in the city of Ensenada, Buenos Aires Province (2010-2017). The project is materialized through murals with a mosaic technique placed in the neighbourhoods to which the people celebrated belonged. The methodological approach led to the carrying out of twenty-nine interviews of members of the group, relatives and acquaintances which were treated as oral sources and representative stories, allowing understanding and interpretation of the feelings which resulted from the deeds on the local scale: the memories of Ensenada.